Addition of HIV self-test kits to partner notification services to increase HIV testing of male partners of pregnant women in Zambia: two parallel randomised trials. Issue 12 (December 2021) - Mutale, Wilbroad; Freeborn, Kellie; Graybill, Lauren A; Lusaka, Mildred M; Mollan, Katie R; Mweemba, Oliver; Kasaro, Margaret; Lungu, Rose; Kumwenda, Andrew; Saidi, Friday; Powers, Kimberly A; Maman, Suzanne; et al.
Summary: Background: Testing men for HIV during their partner's pregnancy can guide couples-based HIV prevention and treatment, but testing rates remain low. We investigated a combination approach, using evidence-based strategies, to increase HIV testing in male partners of HIV-positive and HIV-negative pregnant women. Methods: We did two parallel, unmasked randomised trials, enrolling pregnant women who had an HIV-positive test result documented in their antenatal record (trial 1) and women who had an HIV-negative test result documented in their antenatal record (trial 2) from an antenatal setting in Lusaka, Zambia. Women in both trials were randomly assigned (1:1) to the intervention or control groups using permuted block randomisation. The control groups received partner notification services only, including an adapted version for women who were HIV-negative; the intervention groups additionally received targeted education on the use of oral HIV self-test kits for their partners, along with up to five oral HIV self-test kits. At the 30 day follow-up we collected information from pregnant women about their primary male partner's HIV testing in the previous 30 days at health-care facilities, at home, or at any other facility. Our primary outcome was reported male partner testing at a health facility within 30 days following randomisation using a complete-case approach. Women also reported male partner HIV testing of any kind (including self-testing at home) that occurred within 30 days. Randomisation groups were compared via probability difference with a corresponding Wald-based 95% CI. The trial is registered at ClinicalTrials.gov (NCT04124536 ) and all enrolment and follow-up has been completed. Findings: From Oct 28, 2019, to May 26, 2020, 116 women who were HIV-positive (trial 1) and 210 women who were HIV-negative (trial 2) were enrolled and randomly assigned to study groups. Retention at 30 days was 100 (86%) in trial 1 and 200 (95%) in trial 2. Women in the intervention group were less likely to report facility-based male partner HIV testing in trial 1 (3 [6%] of 47 vs 15 [28%] of 53, estimated probability difference –21·9% [95% CI –35·9 to –7·9%]) and trial 2 (3 [3%] of 102 vs 33 [34%] of 98, estimated probability difference –30·7% [95% CI –40·6 to –20·8]). However, reported male partner HIV testing of any kind was higher in the intervention group than in the control group in trial 1 (36 [77%] of 47 vs 19 [36%] of 53, estimated probability difference 40·7% [95% CI 23·0 to 58·4%]) and trial 2 (80 [78%] of 102 vs 54 [55%] of 98, estimated probability difference 23·3% [95% CI 10·7 to 36·0%]) due to increased use of HIV self-testing. Overall, 14 male partners tested HIV-positive. Across the two trials, three cases of intimate partner violence were reported (two in the control groups and one in the intervention groups). Interpretation: Our combination approach increased overall HIV testing in male partners of pregnant women but reduced the proportion of men who sought follow-up facility-based testing. This combination approach might reduce linkages to health care, including for HIV prevention, and should be considered in the design of comprehensive HIV programmes. Funding: National Institutes of Health.